PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN ONLINE SHOP LAZADA DI KOTA BATAM - SITEPU, RINALDO; Sukati, Inda (LPPM Universitas Putera Batam, 2023)
The aims of this Study is to investigate the effect of product quality and brand image on buyingdecision of Lazada online Store in Batam data was collected through questionaire with totalresponden 204. The research finding showed that brand image has a positive and significanteffect on purchasing decisions. The t test on product quality (X1) is obtained 11.778 > t table1.972 and 0.000 significant < 0.05. This means that product quality has a positive and significanteffect on purchasing decisions. So the first hypothesis can be accepted. The t test on brandimage (X2) obtained 14.670 > t table 1.972 and 0.000 significant <0.05. This means that brandimage has a positive and significant effect on purchasing decisions. Then the second hypothesiscan be accepted. Based on the research, there is a link between product quality and brand imageon the purchasing decision of the Lazada online shop. This implies that there is an important rolefor product quality, brand image on purchasing decisions